Degradation of iopamidol by UV365/NaClO: Roles of reactive species, degradation mechanism, and toxicology. (15th August 2022) - Luo, Congwei; Li, Ming'an; Cheng, Xiaoxiang; Wu, Daoji; Tan, Fengxun; Li, Zhiquan; Chen, Yongkai; Yu, Fan; Ma, Qiao
Highlights: UV365 /NaClO is suitable for the degradation of iopamidol (IPM). ClO·, HO·, and Cl2 − · played the most important roles in the degradation of IPM. Reaction mechanisms, such as H-extraction and amide hydrolysis, were proposed. HOI accumulated during the removal of IPM, which need to be paid attention to. Abstract: The degradation of iopamidol (IPM) was investigated using a UV365 /NaClO system. The reactive species (HO·, ClO·, ozone, Cl·, and Cl 2 − ·) in the system were identified, and the changing trends of the percentage contributions of these reactive species to IPM removal under various conditions were systematically evaluated. The results showed that ClO· and HO· played the most significant roles in the apparent pseudo-first-order rate constants of IPM degradation ( k obs, min −1 ) in the control experiment, and their percentage contributions to k obs were 41.31% and 34.45%, respectively. In addition, Cl· and Cl 2 − · together contributed 22% to the k obs . Furthermore, the contribution of ozone to the IPM removal could be neglected. The concentrations of these species increased significantly when the concentration of NaClO was increased from 50 µM to 200 µM, while the percentage contribution of ClO· to k obs was greatly increased. The concentrations and percentage contributions of HO· and ClO· decreased significantly as the solution pH increased from 5 to 9, with Cl 2 − · playing a greater role in the degradation of IPM under alkaline conditions. While Cl − or HCO3 − /CO3 2− significantly promoted the generation of Cl 2 − · or CO3 − ·, neither had an obvious effect on k obs, suggesting that Cl 2 − · and CO3 − · should have a certain reactivity with IPM. Compared with that of Cl 2 − ·, the percentage contribution of ClO· and Cl· to k obs was more likely to be inhibited by NOM. In addition, the organic and inorganic oxidation products of IPM were detected. The oxidation mechanisms of IPM degradation in the UV365 /NaClO system, such as the H-extraction reaction, deiodination, substitution reaction, amide hydrolysis, and amine oxidation, were proposed according to the obtained 15 organic products. No effect on acute toxicity towards Vibrio fischeri and Photobacterium phosphoreum was detected during the oxidation of IPM by the UV365 /NaClO system. Furthermore, the engineering feasibility of the oxidation system was demonstrated, by the effective degradation of IPM in actual water. However, HOI rapidly accumulated during the removal of IPM in the UV365 /NaClO system, which poses certain environmental risks and will needs to be investigated. Graphical abstract: Image, graphical abstract